Uso de evidências em direitos humanos: Histórico e desafios para o caso brasileiro - Maurício Mota Saboya Pinheiro; Natália Massaco Koga; Luiza Gomes Luz Rosa (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
The aim of this discussion is to contribute to the institutionalization of public policies in the area of human rights, specifically with regard to the governance of the use of evidence in this area. The aim is to indirectly support the strengthening of the analytical capacity of the Brazilian state. This text discuss and synthesize the literature that will serve as a backdrop for the next stages of the research. It aims to answer the following questions: i) what are the specificities of human rights policies that condition the process of institutionalizing the use of evidence? ii) in Brazil, despite its historical development in the production of human rights indicators and information systems, what gaps remain in this area? iii) what does the specialized literature recommend in terms of institutionalizing the use of evidence - including indicators and information systems - in human rights? Finally, a roadmap is proposed for refining the questions and designing the empirical stages of this project, to be carried out in the near future.
Keywords: Z18; K38; D63; 330; evidence-informed public policies; human rights policies; institutionalization